Urease activity in Trichophyton mentagrophytes - Sanyal, A K; Banerjee, A B (Folia microbiologica, 1983)
Urease activity was detected in the dermatophyte Trichophyton mentagrophytes cells at early exponential phase of growth. Specific activity of urease decreased with culture age. At exogenous urea concentrations above 2 mM formation of urease was inhibited. The pH optimum lay at 7-7.5, the Km being 14 mM. No urease activity could be detected in cell-free culture fluid of T. mentagrophytes. No endo- or exocellular urease activity could be detected in a T. rubrum strain grown with or without urea.
Keywords: Ammonia; Trichophyton; Urea; močovina; Hydrogen-Ion Concentration; amoniak; koncentrace vodíkových iontů; Urease; ureasa